MEDIA PEMBELAJARAN TEMATIK PADA PENDIDIKAN ISLAM - Sakinah, Ruh; Nurkholifah, Anisa; Hijjah, Shifany Maulida (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Islamic education plays a strategic role in shaping individuals who are faithful, knowledgeable, and possess noble character through a holistic and meaningful learning process. Along with the development of modern educational paradigms, the thematic learning approach has emerged as an effective alternative, as it is capable of integrating various competencies, learning materials, and Islamic values into a unified theme that is contextual to students’ lives. However, the success of thematic learning cannot be separated from the use of appropriate, innovative learning media that align with students’ characteristics within the context of Islamic education. Thematic learning media are designed as tools to facilitate the teaching and learning process by integrating various subjects into a single theme. This article aims to comprehensively discuss the definition, functions, types, as well as the strengths and weaknesses of thematic learning media. This study employs a literature review method by examining books, journal articles, proceedings, handbooks, and reliable online sources. The findings indicate that thematic learning media can enhance students’ learning motivation, conceptual understanding, and critical thinking skills. Nevertheless, challenges such as limited facilities, teachers’ creativity, and production costs remain obstacles in its implementation. This study is expected to provide insights for teachers, educational practitioners, and policymakers to further optimize thematic learning media in accordance with the demands of the 21st-century curriculum.